Carbon nanotube-coated carbon-coated manganese titanium vanadium sodium phosphate composite positive electrode material and preparation thereof

By adopting carbon nanotubes and then coated carbon-coated manganese titanium vanadium sodium composite positive electrode material, the problem of high energy consumption and poor performance of the synthesis of existing sodium ion battery positive electrode materials is solved, and high performance and low cost are achieved Preparation of cathode material, suitable for large-scale production.

CN119409155APending Publication Date: 2025-02-11GUANGNA MINGSHANG NEW ENERGY TECH (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475651.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have problems such as high synthesis temperature, high energy consumption, poor cycle stability, low working potential, poor rate performance, high production costs, poor economic benefits and environmental benefits.

Method used

The preparation method of carbon nanotubes are adopted to coat carbon nanotubes with carbon coated manganese titanium vanadium sodium vanadium sodium composite positive electrode material, and the combination of titanium citrate complex solution, vanadium salt, manganese salt, phosphate, etc. is formed and re-packed carbon nanotubes are formed by heat treatment. Covered carbon-clad composite material.

Benefits of technology

This method reduces the process steps of the material synthesis, reduces energy consumption, improves material conductivity, controls costs, is suitable for large-scale production, and significantly improves the energy and power characteristics of the cathode material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a carbon nanotube-coated carbon-coated manganese titanium vanadium sodium phosphate composite positive electrode material and a preparation method thereof. The preparation method comprises the following steps: (1) firstly preparing a citric acid titanium complex solution; (2) preparing a citric acid aqueous solution, and adding vanadium salt, manganese salt, phosphate, the titanium complex solution and sodium salt into the citric acid aqueous solution to prepare a mixed solution; (3) heating the mixed solution, and carrying out heat preservation to obtain first precursor sol; (4) adding a carbon nanotube absolute ethyl alcohol dispersion liquid into the first precursor sol, and uniformly stirring to obtain a second precursor sol; (5) performing spray drying to obtain a precursor; and (6) sintering in a protective gas atmosphere, and then cooling and crushing to obtain the composite material. The preparation method disclosed by the invention is feasible in operation and controllable in cost, carbon nanotube channels with electron conduction, sodium ion conduction and high heat conduction are formed in situ in the particles of the obtained positive electrode material, and the energy and power characteristics of the positive electrode material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a carbon nanotube-coated carbon-coated manganese titanium vanadium sodium phosphate composite positive electrode material and its preparation. Background Art

[0002] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Energy is stored and released through the redox reaction of sodium ions at the positive and negative electrodes. The core components of sodium-ion batteries include positive electrodes, negative electrodes and electrolytes. During charging, sodium ions are released from the positive electrode active material and embedded in the negative electrode active material; during discharge, sodium ions are released from the negative electrode active material and embedded in the positive electrode active material. At present, the positive electrode materials used in sodium-ion batteries mainly include layered metal oxides, Prussian blue or Prussian white compounds, and polyanion positive electrode materials. They generally have many problems such as high synthesis temperature, high energy consumption, poor cycle stability, low working potential, unsatisfactory rate performance, high production cost, poor economic and environmental benefits, etc.

[0003] The polyanionic manganese titanium vanadium sodium phosphate cathode composite material NMTVP@C has significant advantages such as high operating voltage. However, due to the low intrinsic conductivity of its pure phase material, it seriously affects the sodium storage electrochemical performance of this type of cathode material, showing low sodium storage specific capacity, poor long-cycle stability and high-rate performance.

[0004] Based on the above-mentioned technical problems, the present invention comes from this. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a carbon nanotube-coated carbon-coated manganese titanium vanadium sodium phosphate composite positive electrode material (NMTVP@C@CNTs) and its preparation. The preparation method is easy to operate, the obtained product has excellent performance, the cost is controllable, and it is suitable for large-scale production.

[0006] The technical solution of the present invention is:

[0007] The present invention relates to a method for preparing a carbon nanotube-coated carbon-coated manganese titanium vanadium sodium phosphate composite positive electrode material, comprising the following steps:

[0008] (1) first preparing a titanium citrate complex solution;

[0009] (2) preparing a citric acid aqueous solution, and then adding a vanadium salt, a manganese salt, a phosphate solution, a titanium citrate complex solution, and a sodium salt to the citric acid aqueous solution to prepare a mixed solution; the titanium citrate complex has a molecular formula of: Ti2O2(OH)2C6H5O7.3H2O, and is named: trihydrate dihydroxydititanyl citrate;

[0010] (3) heating the mixed solution obtained in step (2) to 80° C. and keeping the temperature for 60-120 minutes to obtain a first precursor sol;

[0011] (4) adding the carbon nanotube anhydrous ethanol dispersion to the first precursor sol and stirring evenly to obtain a second precursor sol;

[0012] (5) spray drying the second precursor sol to obtain a precursor;

[0013] (6) The precursor is sintered under a protective gas atmosphere, and then cooled and crushed to obtain carbon nanotubes and then coated with carbon to obtain a composite positive electrode material NMTVP@C@CNTs.

[0014] Preferably, the preparation of the titanium citrate complex solution specifically comprises the following steps:

[0015] a. React high-purity TiO2 with concentrated sulfuric acid to obtain a high-purity titanyl sulfate solution; wherein the molecular formula of titanyl sulfate hydrate is: TiOSO4.H2SO4.3H2O;

[0016] b. Adding ammonia water to the high-purity titanyl sulfate solution obtained in step a, adjusting the pH to 3-4, and generating a white metatitanic acid precipitate;

[0017] c. Filter and wash the product obtained in step b until the filtrate is neutral and no sulfate ions remain, thereby obtaining a metatitanic acid precipitate product; this step can remove ammonium sulfate to meet the production of positive electrode materials for sodium ion batteries;

[0018] d. Prepare a citric acid aqueous solution, add the titanic acid precipitate obtained in step c into the citric acid aqueous solution, stir evenly, dissolve the titanic acid precipitate, and obtain a citrate titanium complex solution.

[0019] Preferably, in step a, SO4 in concentrated sulfuric acid 2- The molar ratio of Ti to high-purity TiO2 is 2:1, the purity of high-purity TiO2 is 99.5%, the reaction temperature in the closed reactor is 120°C, and the reaction time is 2h.

[0020] Preferably, the mass concentration of concentrated sulfuric acid used in step a is preferably 98%, and the ammonia water used in step b is a pH control agent, and the mass concentration of the ammonia water is preferably 25-28%.

[0021] Preferably, the molar ratio of citric acid in step d to Ti in the high-purity TiO2 in step a is 1:2.

[0022] Preferably, in terms of molar ratio, high-purity water: citric acid: vanadium salt: manganese salt: phosphate: TiO2: sodium salt = (360-370): 1: (0.2-0.5): 1: 3: (0.8-0.5): (3.2-3.5), wherein the molar amount of citric acid represents the total molar amount of citric acid used in step d and step (2), the phosphate is added in the form of a solution, the phosphate is added to high-purity water and dissolved to obtain a phosphate solution, and the molar amount of high-purity water represents the total molar amount of high-purity water used to prepare the mixed solution in step (2).

[0023] Preferably, in step (2), the manganese salt is manganese acetate, the vanadium salt is ammonium metavanadate, the phosphate is ammonium dihydrogen phosphate, and the sodium salt is sodium acetate; each salt is added separately and stirred for 10-30 minutes, preferably 5-10 minutes, after addition.

[0024] Preferably, in step (5), the spray drying inlet temperature is required to be controlled at 300-350°C, and the outlet temperature is required to be controlled at 105-108°C.

[0025] Preferably, in step (6), the sintering conditions are: in a protective gas atmosphere, heating to 680-700° C. in 240-360 minutes and keeping the temperature for 8-18 hours.

[0026] The present invention also relates to a carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material. The carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material is prepared by the above-mentioned preparation method, and the molecular formula is expressed as: Na 3+x MnTi 1-x V x (PO4)3C@C@CNTs, where x=0.2-0.5.

[0027] Preferably, the carbon content of the carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material is 8-10%.

[0028] The beneficial effects of the present invention are:

[0029] (1) The preparation method of the present invention helps to simplify the process steps of material synthesis, the investment in nano-sand milling equipment is almost zero, and energy consumption is reduced. Sol spray drying can effectively control the particle size of the synthetic material and enhance the conductivity of the carbon-coated manganese titanium vanadium sodium phosphate composite material NMTVP@C@CNTs coated with carbon nanotubes;

[0030] (2) The present invention uses high-purity TiO2 as a titanium source, which has a wide range of sources and can reduce sand mill investment and energy consumption, with controllable costs and good economic benefits;

[0031] (3) The preparation method of the present invention is feasible and cost-controllable. The obtained positive electrode material particles in situ form carbon nanotube channels with electronic conductivity, sodium ion conductivity and high thermal conductivity, which greatly improves the energy and power characteristics of the positive electrode material. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0033] Embodiment 1:

[0034] Carbon nanotubes coated with carbon coated manganese titanium vanadium sodium phosphate composite positive electrode material Na 3+x MnTi 1-x V x Preparation of (PO4)3@C@CNTs (where x=0.2):

[0035] S1. Weigh 3.2107 g of high-purity TiO2 with a purity of 99.5%, add it to 8 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, and carry out hydrothermal reaction in a closed reactor at 120°C for 2 h. After cooling, add 15 g of high-purity water to obtain a high-purity titanyl sulfate solution with a solid content of 39.36%.

[0036] S2. Add 10.88 g of 25% ammonia water to the high-purity titanyl sulfate solution obtained in step S1, adjust the pH to 3, and obtain a white metatitanic acid precipitate.

[0037] S3. Use G4 filter crucible and pure water to wash the titanic acid precipitate. The pH of the filtrate is 7, and there is no residual sulfate ion.

[0038] S4. Weigh 3.8814 g of anhydrous citric acid with a purity of 99%, dissolve it in 100 g of high-purity water, add the cleaned metatitanic acid precipitate produced in S2 and S3 to the citric acid aqueous solution, stir evenly, and obtain 119.8764 g of citrate titanium complex solution.

[0039] S5. Weigh 5.8221 g of anhydrous citric acid with a purity of 99%, and dissolve it in 100 g of high-purity water to obtain a citric acid aqueous solution.

[0040] S6. Weigh 1.1757 g of ammonium metavanadate with a purity of 99.5%, add it to the solution obtained in step S5, and stir for 10 minutes.

[0041] S7. Weigh 12.3785 g of manganese acetate tetrahydrate with a purity of 99.0%, add it to the citric acid aqueous solution in which ammonium metavanadate is dissolved obtained in step S6, and stir for 10 minutes.

[0042] S8. Weigh 17.4285 g of ammonium dihydrogen phosphate with a purity of 99.0%, add it to 120 g of high-purity water, and add it to the mixed aqueous solution obtained in step S7 after it dissolves, and stir for 10 minutes.

[0043] S9. Add 119.8764 g of the titanium citrate complex solution prepared in S4 to the solution obtained in step S8 and stir for 10 minutes.

[0044] S10. Weigh 13.2574 g of anhydrous sodium acetate with a purity of 99%, add it to the mixed solution obtained in step S9, and stir for 10 minutes to obtain a mixed solution.

[0045] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.2 MnTi 0.8 V 0.2 (PO4)3@C first precursor sol 249g.

[0046] S12, weigh 28 g of anhydrous ethanol dispersion of carbon nanotubes with a solid content of 0.05% prepared by ultrasonication, add it to 249 g of the first precursor sol, and stir evenly to obtain 277 g of the second precursor sol.

[0047] S13, controlling the air inlet temperature at 350°C and the air outlet temperature at 108°C, spray drying the second precursor sol, and obtaining 51.43 g of the precursor.

[0048] S14. Under inert gas atmosphere (N2), the above-mentioned positive electrode material precursor is heated to 680°C for 240 minutes and kept warm for 8 hours, then cooled and crushed with a small airflow mill to obtain a carbon-coated vanadium titanium manganese phosphate sodium composite positive electrode material coated with carbon nanotubes. The cumulative particle size distribution numbers are measured as follows: D10=1.25μm, D50=2.85μm, D90=5.64μm, Dmax=12.58μm, and the carbon content of the material is 8.85%.

[0049] Embodiment 2:

[0050] Carbon nanotubes coated with carbon coated manganese titanium vanadium sodium phosphate composite positive electrode material Na 3+x MnTi 1-x V x Preparation of (PO4)3@C@CNTs (where x=0.3):

[0051] S1. Weigh 2.8094 g of high-purity TiO2 with a purity of 99.5%, add it to 7 g of 98% concentrated sulfuric acid, stir evenly, and react in a closed reactor at 120 degrees for 2 hours. After cooling, add 13.2 g of high-purity water to obtain a high-purity titanyl sulfate solution with a solid content of 39.35%.

[0052] S2. Add 9.52 g of 25% aqueous ammonia to the high-purity titanyl sulfate solution obtained in step S1, adjust the pH to 3, and obtain a white metatitanic acid precipitate.

[0053] S3. Use G4 filter crucible and pure water to wash the titanic acid precipitate. The pH of the filtrate is 7, and there is no residual sulfate ion.

[0054] S4. Weigh 3.3963 g of anhydrous citric acid with a purity of 99%, dissolve it in 100 g of high-purity water, add the cleaned metatitanic acid precipitate produced in S2 and S3 to the citric acid aqueous solution, stir evenly, and obtain 117.392 g of citrate titanium complex solution.

[0055] S5. Weigh 6.3072 g of anhydrous citric acid with a purity of 99%, and dissolve it in 100 g of high-purity water to obtain a citric acid aqueous solution.

[0056] S6. Weigh 1.773 g of ammonium metavanadate with a purity of 99.5%, add it to the solution obtained in step S5, and stir for 10 minutes.

[0057] S7. Weigh 12.3785 g of manganese acetate tetrahydrate with a purity of 99.0%, add it to the citric acid aqueous solution in which the ammonium metavanadate was dissolved obtained in step S6, and stir for 10 minutes.

[0058] S8. Weigh 17.4285 g of ammonium dihydrogen phosphate with a purity of 99.0%, add it to 120 g of high-purity water, and add it to the mixed aqueous solution obtained in step S7 after it dissolves, and stir for 10 minutes.

[0059] S9. Add 117.392 g of the titanium citrate complex solution prepared in S4 to the solution obtained in step S8 and stir for 10 minutes.

[0060] S10. Weigh 13.6717 g of anhydrous sodium acetate with a purity of 99%, add it to the mixed solution obtained in step S9, and stir for 10 minutes to obtain a mixed solution.

[0061] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.3 MnTi 0.7 V 0.3 (PO4)3@C first precursor sol 246g.

[0062] S12, weigh 28 g of carbon nanotube anhydrous ethanol dispersion with a solid content of 0.05% prepared by ultrasonication, add it to 246 g of the first precursor sol, and stir evenly to obtain 274 g of the second precursor sol.

[0063] S13, controlling the air inlet temperature at 350°C and the air outlet temperature at 108°C, spray drying the second precursor sol, and obtaining 51.31 g of the precursor.

[0064] S14. Under inert gas atmosphere (N2), the above-mentioned positive electrode material precursor is heated to 680°C for 240 minutes and kept warm for 8 hours, then cooled and crushed with a small airflow mill to obtain carbon-coated vanadium titanium manganese sodium phosphate composite positive electrode material coated with carbon nanotubes. The cumulative particle size distribution numbers are measured as follows: D10=1.45μm, D50=4.24μm, D90=6.68μm, Dmax=14.56μm, and the carbon content C of the material is 8.76%.

[0065] Embodiment 3:

[0066] Carbon nanotubes coated with carbon coated manganese titanium vanadium sodium phosphate composite positive electrode material Na 3+x MnTi 1-x V x Preparation of (PO4)3@C@CNTs (where x=0.4):

[0067] S1. Weigh 2.408 g of high-purity TiO2 with a purity of 99.5%, add it to 6 g of 98% concentrated sulfuric acid, stir evenly, react in a closed reactor at 120 degrees for 2 hours, add 11.5 g of high-purity water to obtain a high-purity titanyl sulfate solution with a solid content of 39.34%.

[0068] S2. Add 8.16 g of 25% aqueous ammonia to the high-purity titanyl sulfate solution obtained in step S1, adjust the pH to 3, and obtain a white metatitanic acid precipitate.

[0069] S3. Use G4 filter crucible and pure water to wash the titanic acid precipitate. The pH of the filtrate is 7, and there is no residual sulfate ion.

[0070] S4. Weigh 2.9111 g of anhydrous citric acid with a purity of 99%, dissolve it in 100 g of high-purity water, add the cleaned metatitanic acid precipitate produced in S2 and S3 to the citric acid aqueous solution, stir evenly, and obtain 121.6061 g of citrate titanium complex solution.

[0071] S5. Weigh 6.7924 g of anhydrous citric acid with a purity of 99%, and dissolve it in 100 g of high-purity water to obtain a citric acid aqueous solution.

[0072] S6. Weigh 2.364 g of ammonium metavanadate with a purity of 99.5%, add it to the solution obtained in step S6, and stir for 10 minutes.

[0073] S7. Weigh 12.3785 g of manganese acetate tetrahydrate with a purity of 99.0%, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.

[0074] S8. Weigh 17.4285 g of ammonium dihydrogen phosphate with a purity of 99.0%, add 120 g of high-purity water, dissolve it and add it to the mixed aqueous solution obtained in S7, and stir for 10 minutes.

[0075] S9. Add 121.6061 g of the titanium citrate complex solution prepared in S4 to the solution obtained in step S8 and stir for 10 minutes.

[0076] S10. Weigh 14.086 g of anhydrous sodium acetate with a purity of 99%, add it to the mixed solution obtained in step S9, and stir for 10 minutes to obtain a mixed solution.

[0077] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.4 MnTi 0.6 V 0.4 (PO4)3@C first precursor sol 247g.

[0078] S12, weigh 28 g of carbon nanotube anhydrous ethanol dispersion with a solid content of 0.05% prepared by ultrasonication, add it to 247 g of the first precursor sol, and stir evenly to obtain 275 g of the second precursor sol.

[0079] S13, controlling the air inlet temperature at 350°C and the air outlet temperature at 108°C, spray drying the second precursor sol, and obtaining 51.12 g of the precursor.

[0080] S14. Under inert gas atmosphere (N2), the above-mentioned positive electrode material precursor is heated to 680°C for 240 minutes and kept warm for 8 hours, then cooled and crushed with a small airflow mill to obtain a carbon-coated vanadium titanium manganese phosphate sodium composite positive electrode material coated with carbon nanotubes. The cumulative particle size distribution numbers are measured as follows: D10=1.52μm, D50=4.21μm, D90=6.87μm, Dmax=15.21μm, and the carbon content C of the material is 8.35%.

[0081] Example 4

[0082] Carbon nanotubes coated with carbon coated manganese titanium vanadium sodium phosphate composite positive electrode material Na 3+x MnTi 1-x V x Preparation of (PO4)3@C@CNTs (where x=0.5):

[0083] S1. Weigh 2.0067 g of high-purity TiO2 with a purity of 99.5%, add it to 5 g of 98% (mass concentration) concentrated sulfuric acid, stir evenly, react in a closed reactor at 120 degrees for 2 hours, add 9.5 g of high-purity water to obtain a high-purity titanyl sulfate solution with a solid content of 39.35%.

[0084] S2. Add 6.8 g of 25% ammonia water to the high-purity titanyl sulfate solution obtained in step S1, adjust the pH to 3, and obtain a white metatitanic acid precipitate.

[0085] S3. Use G4 filter crucible and pure water to wash the titanic acid precipitate. The pH of the filtrate is 7, and there is no residual sulfate ion.

[0086] S4. Weigh 2.4259 g of anhydrous citric acid with a purity of 99%, dissolve it in 100 g of high-purity water, add the cleaned metatitanic acid precipitate produced in S2 and S3 to the citric acid aqueous solution, stir evenly, and obtain 119.4474 g of citrate titanium complex solution.

[0087] S5. Weigh 7.2776 g of anhydrous citric acid with a purity of 99%, and dissolve it in 100 g of high-purity water to obtain a citric acid aqueous solution.

[0088] S6. Weigh 2.9559 g of ammonium metavanadate with a purity of 99.5%, add it to the solution obtained in step S6, and stir for 10 minutes.

[0089] S7. Weigh 12.3785 g of manganese acetate tetrahydrate with a purity of 99.0%, add it to the citric acid aqueous solution obtained in step S5, and stir for 10 minutes.

[0090] S8. Weigh 17.4285 g of ammonium dihydrogen phosphate with a purity of 99.0%, add 120 g of high-purity water, and add the dissolved ammonium dihydrogen phosphate to the mixed aqueous solution obtained in step S8, and stir for 10 minutes.

[0091] S9. Add 119.4474 g of the titanium citrate complex solution prepared in S4 to the solution obtained in step S7 and stir for 10 minutes.

[0092] S10. Weigh 14.509 g of anhydrous sodium acetate with a purity of 99%, add it to the mixed solution obtained in step S9, and stir for 10 minutes to obtain a mixed solution.

[0093] S11, heat the mixed solution to 80°C and keep it warm for 120 minutes to obtain Na 3.5 MnTi 0.5 V 0.5 (PO4)3@C first precursor sol 244g.

[0094] S12, weigh 28 g of anhydrous ethanol dispersion of carbon nanotubes with a solid content of 0.05% prepared by ultrasonication, add it to 244 g of the first precursor sol, and stir evenly to obtain 268 g of the second precursor sol.

[0095] S13, controlling the air inlet temperature at 350°C and the air outlet temperature at 108°C, spray drying the second precursor sol, and obtaining 51.1 g of the precursor.

[0096] S14. Under inert gas atmosphere (N2), the above-mentioned positive electrode material precursor is heated to 680°C for 240 minutes and kept warm for 8 hours, then cooled and crushed with a small airflow mill to obtain carbon-coated vanadium titanium manganese sodium phosphate composite positive electrode material coated with carbon nanotubes. The cumulative particle size distribution numbers are measured as follows: D10=1.55μm, D50=4.32μm, D90=6.86μm, Dmax=14.52μm, and the carbon content C of the obtained material is 8.05%.

[0097] Comparative Example 1

[0098] The method is carried out on the basis of Example 1, except that after obtaining the first precursor sol, the CNTs are not coated and the process is directly spray-dried.

[0099] (1) According to the steps of Example 1, 249 g of the precursor sol obtained in step S11 was obtained.

[0100] (2) The inlet air temperature was controlled at 350°C and the outlet air temperature was controlled at 108°C. The precursor sol was spray dried to obtain 49.8 g of the precursor.

[0101] (3) Under inert gas atmosphere (N2), the above cathode material precursor was heated to 680°C for 240 minutes and kept at this temperature for 8 hours, then cooled and crushed with a small airflow mill to obtain a carbon-coated vanadium titanium manganese sodium phosphate composite cathode material without carbon nanotubes. The cumulative particle size distribution numbers were measured as follows: D10 = 1.83 μm, D50 = 4.83 μm, D90 = 7.65 μm, Dmax = 16.58 μm, and the carbon content of the material was 4.45%.

[0102] Comparative Example 2

[0103] The method is carried out on the basis of Example 2, except that after obtaining the first precursor sol, the CNTs are not coated and the process is directly spray-dried.

[0104] (1) According to the steps of Example 2, 246 g of the precursor sol obtained in step S11 was obtained.

[0105] (2) The inlet air temperature was controlled at 350°C and the outlet air temperature was controlled at 108°C. The precursor sol of Comparative Example 2 was spray dried to obtain 48 g of the precursor.

[0106] (3) Under inert gas atmosphere (N2), the positive electrode material precursor is heated to 680°C for 240 minutes and kept at this temperature for 8 hours, then cooled and crushed with a small air flow mill to obtain a carbon-coated vanadium titanium manganese sodium phosphate composite positive electrode material without carbon nanotubes. The measured cumulative particle size distribution numbers are: D10 = 1.85 μm, D50 = 4.88 μm, D90 = 7.66 μm, Dmax = 17.12 μm, and the carbon content C of the material is 3.45%.

[0107] Comparative Example 3

[0108] The method is carried out on the basis of Example 3, except that after obtaining the first precursor sol, the CNTs are not coated and the process is directly spray-dried.

[0109] (1) According to the steps of Example 3, 247 g of the precursor sol obtained in step S11 was obtained.

[0110] (2) The inlet air temperature was controlled at 350°C and the outlet air temperature was controlled at 108°C, and the second precursor sol was spray dried to obtain 46 g of the precursor.

[0111] (3) Under inert gas atmosphere (N2), the positive electrode material precursor is heated to 680°C for 240 minutes and kept at this temperature for 8 hours, then cooled and crushed with a small air flow mill to obtain a carbon-coated vanadium titanium manganese sodium phosphate composite positive electrode material without carbon nanotubes. The measured cumulative particle size distribution numbers are: D10 = 1.87 μm, D50 = 4.89 μm, D90 = 7.86 μm, Dmax = 17.55 μm, and the carbon content C of the material is 3.05%.

[0112] Comparative Example 4

[0113] The method is carried out on the basis of Example 4, except that after obtaining the first precursor sol, the CNTs are not coated and the process is directly spray-dried.

[0114] (1) According to the steps of Example 4, 244 g of the precursor sol obtained in step S11 was obtained.

[0115] (2) The air inlet temperature was controlled at 350°C and the air outlet temperature was controlled at 108°C, and the second precursor sol was spray dried to obtain 45 g of the precursor.

[0116] (3) Under inert gas atmosphere (N2), the above cathode material precursor was heated to 680°C for 240 minutes and kept at this temperature for 8 hours, then cooled and crushed with a small air flow mill to obtain a carbon-coated vanadium titanium manganese sodium phosphate composite cathode material coated with carbon nanotubes. The cumulative particle size distribution numbers were measured as follows: D10 = 1.2 μm, D50 = 2.8 μm, D90 = 5.6 μm, Dmax = 11.5 μm, and the carbon content C of the obtained material was 2.82%.

[0117] Application Examples

[0118] 2025-type button cells were used to evaluate the electrochemical performance of the materials.

[0119] The button cell was prepared with a CR2025 battery shell (i.e., 20 mm in diameter and 2.5 mm in thickness) for electrochemical performance testing and evaluation. The sodium ion positive electrode material used in the preparation of the pole piece was: CNT: VGCF: PVDF mass ratio 92: 0.8: 3.2: 4, using oil-based solvent NMP, and then ground with an agate mortar in a homemade glove box. The ground slurry was coated on aluminum foil using a 200-micron frame film maker, dried in a blast drying oven at 150 degrees for 1 hour, and then the punched pole piece was placed in a vacuum drying oven, and dried at 120°C, -0.1MPa vacuum for 12 hours. Later, a 15.6mm*0.6mm metal sodium sheet was used as the negative electrode to assemble a 2025 button cell, and the electrolyte was 1mol / LNaPF6+EC:PC:FEC (1:1:0.1 volume ratio).

[0120] 1. Remove power and let stand for 6 hours.

[0121] 2. Start constant current charging at 0.1C, and start constant voltage charging when the voltage reaches 4.3V. Charging ends when the constant voltage charging current is less than 0.06C.

[0122] 3. Discharge from 4.3V to 1.5V.

[0123] 4. After the first charge and discharge, start the next charge and discharge process, and set the same procedure as the first charge and discharge process.

[0124] 5, 50, 100, and 500 cycles are repeated in sequence.

[0125] Table 1 Electrochemical performance test results of Examples 1-4

[0126] Example 1 Example 2 Example 3 Example 4 0.1CmAh / g 162.5 161.8 161.4 160.1 First Charge 162.5 161.8 161.4 160.1 Premiere 147.4 146.6 146.1 144.8 Initial efficiency % 90.71% 90.61% 90.52% 90.44% Loop 50 times 95.06% 95.04% 95.03% 95.02% Loop 100 times 90.08% 90.05% 90.03% 90.02% Loop 500 times 88.04% 88.02% 88.01% 88.01%

[0127] Table 2 Electrochemical performance test results of comparative examples 1-4

[0128] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 0.1CmAh / g 148.5 147.8 146.8 146.5 First Charge 148.5 147.8 146.4 145.1 Premiere 131.1 130.4 130.1 130.0 Initial efficiency % 88.28% 88.23% 88.62% 88.74% Loop 50 times 91.89% 91.67% 91.72% 91.55% Loop 100 times 89.08% 89.05% 89.02% 89.01% Loop 500 times 85.02% 84.68% 84.76% 84.43%

[0129] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a composite positive electrode material of carbon nanotubes coated with carbon-coated sodium manganese titanium vanadium phosphate, characterized in that: The following steps are involved: (1) first preparing a titanium citrate complex solution; (2) preparing a citric acid aqueous solution, and then adding a vanadium salt, a manganese salt, a phosphate solution, a titanium citrate complex solution, and a sodium salt to the citric acid aqueous solution to prepare a mixed solution; (3) heating the mixed solution obtained in step (2) to 80° C. and keeping the temperature for 60-120 minutes to obtain a first precursor sol; (4) adding the carbon nanotube anhydrous ethanol dispersion to the first precursor sol and stirring evenly to obtain a second precursor sol; (5) spray drying the second precursor sol to obtain a precursor; (6) The precursor is sintered under a protective gas atmosphere, and then cooled and crushed to obtain carbon nanotubes and then coated with carbon-coated composite positive electrode materials.

2. The preparation method according to claim 1, characterized in that: The preparation of the titanium citrate complex solution specifically comprises the following steps: a. React high-purity TiO2 with concentrated sulfuric acid to obtain a high-purity titanyl sulfate solution; b. Adding ammonia water to the high-purity titanyl sulfate solution obtained in step a, adjusting the pH to 3-4, and generating a white metatitanic acid precipitate; c. Filter and wash the product obtained in step b until the filtrate is neutral to obtain a metatitanic acid precipitate product; d. Prepare a citric acid aqueous solution, add the metatitanic acid precipitate obtained in step c to the citric acid aqueous solution, stir evenly, and obtain a citrate titanium complex solution.

3. The preparation method according to claim 2, characterized in that: In step a, SO4 in concentrated sulfuric acid 2- The molar ratio of Ti to high-purity TiO2 is 2:1, and the purity of high-purity TiO2 is 99.5%. The reaction temperature in the closed reactor is 120° C., and the reaction time is 2 hours.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the citric acid in step d to the Ti in the high-purity TiO2 in step a is 1:

2.

5. The preparation method according to claim 2, characterized in that: In terms of molar ratio, high-purity water: citric acid: vanadium salt: manganese salt: phosphate: TiO2: sodium salt = (360-370): 1: (0.2-0.5): 1: 3: (0.8-0.5): (3.2-3.5), wherein the molar amount of citric acid represents the total molar amount of citric acid used in step d and step (2), the phosphate is added in the form of a solution, the phosphate is added to high-purity water and dissolved to obtain a phosphate solution, and the molar amount of high-purity water represents the total molar amount of high-purity water used in preparing the mixed solution of step (2).

6. The preparation method according to claim 1, characterized in that: In step (2), the manganese salt is manganese acetate, the vanadium salt is ammonium metavanadate, the phosphate is ammonium dihydrogen phosphate, and the sodium salt is sodium acetate; each salt is added separately and stirred for 10-30 minutes after addition.

7. The preparation method according to claim 1, characterized in that: In step (5), the spray drying inlet temperature is required to be controlled at 300-350°C, and the outlet temperature is required to be controlled at 105-108°C.

8. The preparation method according to claim 1, characterized in that: In step (6), the sintering conditions are: in a protective gas atmosphere, heating to 680-700° C. in 240-360 minutes and keeping the temperature for 8-18 hours.

9. A carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material, characterized in that: The carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material is prepared by the preparation method described in any one of claims 1 to 8, and the molecular formula is: Na 3+x MnTi 1-x V x (PO4)3C@C@CNTs, where x=0.2-0.

5.

10. The carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material according to claim 9, characterized in that: The carbon content of the carbon nanotube-coated carbon-coated sodium manganese titanium vanadium phosphate composite positive electrode material is 7-9%.